Alcohol Intake and Blood Pressure Levels: A Dose-Response Meta-Analysis of Nonexperimental Cohort Studies - Di Federico, Silvia; Filippini, Tommaso; Whelton, Paul K; Cecchini, Marta; Iamandii, Inga; Boriani, Giuseppe; Vinceti, Marco (Hypertension (Dallas, Tex. 1979), 2023)
Alcohol consumption may increase blood pressure but the details of the relationship are incomplete, particularly for the association at low levels of alcohol consumption, and no meta-analyses are available for nonexperimental cohort studies. We performed a systematic search of longitudinal studies in healthy adults that reported on the association between alcohol intake and blood pressure. Our end points were the mean differences over time of systolic (SBP) and diastolic blood pressure (DBP), plotted according to baseline alcohol intake, by using a dose-response 1-stage meta-analytic methodology. Seven studies, with 19 548 participants and a median follow-up of 5.3 years (range, 4-12 years), were included in the analysis. We observed a substantially linear positive association between baseline alcohol intake and changes over time in SBP and DBP, with no suggestion of an exposure-effect threshold. Overall, average SBP was 1.25 and 4.90 mm Hg higher for 12 or 48 grams of daily alcohol consumption, compared with no consumption. The corresponding differences for DBP were 1.14 and 3.10 mm Hg. Subgroup analyses by sex showed an almost linear association between baseline alcohol intake and SBP changes in both men and women, and for DBP in men while in women we identified an inverted -shaped association. Alcohol consumption was positively associated with blood pressure changes in both Asians and North Americans, apart from DBP in the latter group. Our results suggest the association between alcohol consumption and SBP is direct and linear with no evidence of a threshold for the association, while for DBP the association is modified by sex and geographic location.